Factors affecting mental illness and social stress in hospital workers treating COVID-19: Paradoxical distress during pandemic era. (May 2021) - Matsumoto, Yukiko; Fujino, Junya; Shiwaku, Hiroki; Miyajima, Miho; Doi, Satomi; Hirai, Nobuhide; Jitoku, Daisuke; Takagi, Shunsuke; Tamura, Takehiro; Maruo, Takashi; Shidei, Yuki; Kobayashi, Nanase; et al.
Abstract: Background: The coronavirus disease 2019 (COVID-19) has affected all countries in the world. Hospital workers are at high risk of mental illness, such as anxiety and depression. Furthermore, they also face many social stresses, such as deterioration of human relations and income reduction. Apart from mental illness, these social stresses can reduce motivation and lead to voluntary absenteeism, which contribute to a collapse of medical systems. Thus, for maintaining medical systems, it is crucial to clarify risk factors for both mental illness and increased social stress among hospital workers. However, little attention has been paid to factors affecting social stress, and thus, we aimed to address this gap. Methods: In this cross-sectional survey of 588 hospital workers, the levels of anxiety, depression, and social stress were assessed using the 7-item Generalized Anxiety Disorder scale (GAD-7), 9-item Patient Health Questionnaire (PHQ-9), and Tokyo Metropolitan Distress Scale for Pandemic (TMDP). Multiple regression analyses were conducted to identify the demographic variables affecting these problems. Results: Older age and female sex were common risk factors for anxiety, depression, and social stress. Moreover, occupational exposure to COVID-19 and hospital staff other than doctors/fewer non-work days were risk factors for increased anxiety and depression, respectively. Furthermore, living with families/others was a risk factor for increased social stress during this pandemic. Conclusion: Our findings could be useful for developing policies and practices to minimize the risk of mental illness and increased social stress among hospital workers, highlighting that attention should be paid to social factors, such as an individual's household situation. Highlights: Social stress of hospital workers in a pandemic can lead to healthcare collapse. Tokyo Metropolitan Distress Scale for Pandemic (TMDP) assesses social stress. Living with someone is a risk factor for social stress during COVID-19 pandemic. Workers' social situation is a crucial factor for maintaining the healthcare system.